Household headship and child death: Evidence from Nepal - Adhikari Ramesh; Podhisita Chai (BMC, 2010)
Abstract Background Nepal has seen substantial improvements in its reproductive health outcomes, but infant and child mortality are still high. This study attempts to examine the prevalence and factors influencing the experience of child death of mothers who have given birth during a five-year period. More specifically, this paper aims to investigate whether household headship has an impact on child death in Nepal. Methods This paper reports on data drawn from the Nepal Demographic and Health Survey (NDHS 2006), a nationally representative sample survey. The analysis is confined to women who had given birth during the five years preceding the survey (n = 4066). The association between experience of child death of mother and the explanatory variables was assessed via bivariate analysis using a chi-square test. The variables were also examined using multivariate analysis (binary logistic regression) to assess the net effect of household headship on child death after controlling for the other variables. Results Out of all the mothers who had given birth during a five-years period, 3,229 (79.4%) were from male-headed households; the remaining 837 (20.6%) were from female-headed households. A significantly higher proportion of mothers from male-headed households (6.5%) than female-headed households (4.5%) had experienced the death of a child over the five years preceding the survey. Several socio-demographic, economic, and cultural variables were significant predicators for death of a child. For instance, women who had given birth to three or more children and who were Hindu were more likely to experience a child's death than were their counterparts. On the other hand, women who were literate, who had ever used family planning methods, who had visited a health facility, who utilized antenatal care for the last pregnancy, and who were from female-headed households were less likely to see a child die than were women in their comparison group. Notably, keeping all other control variables constant in the logistic model, women from female-headed households were 31 percent less likely to experience the death of a child (odds ratio = 0.69) than were women from male-headed households. Conclusion The death of children is not uncommon in Nepal. No single factor can account for the high child mortality in the country; many factors contribute to the problem. After controlling for other variables, this study found that, among many other factors, household headship was a strong predictor. Programs seeking to help remedy this problem should focus on the issues identified here regarding women's autonomy, such as reducing the number of children born, increasing women's literacy status, increasing the use of family planning, increasing the use of antenatal care, and increasing female household headship so that child mortality will decrease and the overall well-being of the family can be maintained and enhance.